Mothers' Perceptions of Danger Signs in the Third Trimester of Pregnancy - Debora Lestari Simamora; Fitriana Ritonga; Welina Sebayang; Oktiferiani Hura; Ayu Arleka; Adinda Khairunisa; Putri Arimbi; Hertika Sinambela (Griya Eka Sejahtera, 2026)
Background: Pregnancy is a critical period in human development, characterized by the physiological and psychological interactions between the mother and the fetus. During this period, the mother plays an essential role in supporting fetal growth and development until childbirth. In the third trimester, pregnant women must be aware of potential danger signs that may indicate pregnancy-related complications. This study aimed to explore mothers’ perceptions of danger signs during the third trimester of pregnancy.Methods: A descriptive qualitative research design was employed. The study population consisted of 28 third-trimester pregnant women, from whom seven participants were selected as the study sample. The sampling technique used was accidental sampling. The study was conducted at the Independent Midwifery Practice of Hj. Sesmera, located on Jalan Aluminium IV, Tanjung Mulia, Medan City, North Sumatra, Indonesia. Data collection was carried out from May to August 2024.Results: The findings revealed three major themes: mothers’ perceptions regarding the recognition of danger signs, management of danger signs, and sources of information related to danger signs during the third trimester of pregnancy. These themes were further categorized into several subthemes.Conclusion: Mothers’ perceptions of pregnancy danger signs were influenced by multiple sources of information, including healthcare providers, family members, technology, and the community. Among these factors, support from family and healthcare professionals emerged as the most influential in shaping mothers’ perceptions and enhancing their awareness of danger signs during the third trimester of pregnancy.